Cartographies of action research: searching for displacements of the epistemology of the South - Sousa, Lumárya Souza de (2018)
The purpose of this paper is to discuss action research as one of the possibilities for the development of an epistemology of the South, in which scientific knowledge and other ecologies of knowledge can be linked. In this work, we propose a mapping of what has been developed on action research in Brazil, seeking to discuss this dimension of knowledge production from perspectives which seek to break the gap between colonizing and invisibilized science in the geopolitics of scientific knowledge. Thus, our proposal seeks to answer what has been produced on action research in Brazil, who are the actors that are developing this type of research and how it can be understood as belonging to an epistemology of the South.